Trends in Blended Learning Models for High-Level Thinking Skills (HOTS) - Eges Triwahyuni; Pascalian Hadi Pradana (Universitas Pendidikan Ganesha, 2025)
Problems occur based on the field finding that the availability of time and space is limited during the learning process. In traditional classrooms, there is often not enough time to cover the material thoroughly, let alone build critical thinking skills. The aim of this research is to find out how the blended learning model can improve students' thinking skills. This research uses Systematic Literature Review (SLR) analysis with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) method. To collect data, researchers used the Publish or Perish application. Currently, 49 articles from Scopus and 1 article from another application were selected, and then filtered using appropriate and relevant inclusion criteria. The research results show that combining the blended learning model with other learning models and supported by relevant learning media helps improve the assessment of students' HOTS thinking skills. This model allows for more thorough evaluation and encourages students to learn more, think critically, and find creative solutions independently. This results in a learning experience that is deeper, more meaningful, and relevant to real-world challenges. HOTS thinking skills needed for student success in the digital era can be built through a blended learning model that is integrated with appropriate learning models and media.